(untitled) - Burmark, Lynell (San Francisco, 2011)
They Snooze, You Lose, provides a comprehensive guide made especially for teachers and administrators who want to become presentation "stars" in their classrooms, at board meetings, or any time they are in front of an audience
Keywords: Educational innovations,Classrom environment,Computer-assisted instruction,Hướng dẫn máy tính hỗ trợ,Đổi mới giáo dục,Môi trường lớp học